Flows of dehaven fluid in symmetrically curved capillary fissures and tubes - Walicka, Anna; Falicki, Jarosław; Jurczak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, an analytical method for deriving the relationships between the pressure drop and the volumetric flow rate in laminar flow regimes of DeHaven type fluids through symmetrically corrugated capillary fissures and tubes is presented. This method, which is general with regard to fluid and capillary shape, can also be used as a foundation for different fluids, fissures and tubes. It can also be a good base for numerical integration when analytical expressions are hard to obtain due to mathematical complexities.
Keywords: DeHaven fluid; laminar flow; symmetrically corrugated capillaries; capillary fissures or tubes